The effect of planting location and slope direction on the quality of the fruits of the “Golden Delicious” and “Starking Delicious” apple varieties during storage - قره علي, كرم; جرجس مخول; عبد العزيز بوعيسى (Latakia University Journal -Biological Sciences Series, 2024)
The study was conducted during the 2021 and 2022 seasons in three locations with different elevations above sea level where apple cultivation is widespread in the Latakia Governorate, (Kasab 800 m, Slanfeh 1130 m, and Khirbet Solas 350 m). Four orchards were selected on mountain slopes from the four directions of each site studied, and the fruits were collected according to the stage of maturity of each variety, and the fruits were stored in refrigerated warehouses at a temperature of 1 ± 1 °C and a humidity of 90 ± 5% for a period of 4 months. In order to study the effect of the height of the planting site and the direction of the slope on the type and quality of the fruits of the two apple varieties “Golden Delicious” and “Starking Delicious” during the period of cold storage. the results showed a significant and clear effect of the height of the site and the direction of the slope on the characteristics of the fruits of the two varieties “Golden Delicious” and “Starking Delicious” before storage and during the cold storage period. The results showed an increase in the loss rate with increasing storage period. The highest loss rate was recorded in the northern slope of the Khirbet Solas site, 13.12%, followed by the western slope, 13.13%, for the “Golden Delicious” variety. The percentage of loss in fruit weight reached the “Starking” variety at the end of the storage period. It was also observed that the hardness of the fruits decreased with increasing duration of storage, as the hardness of the fruits decreased to 2.47 kg/cm2 in the northern slope of Slanfeh, while in the Kassab site it reached 2.11 kg/cm2 in the northern slope for the “Golden” variety. As for the variety “Starking” the Kassab website recorded an average hardness of 1.88 kg/cm2 for the northern slope. The results showed an increase in the percentage of TSS with increasing storage period. At the end of the storage period, it reached 15.48% on the eastern slope of the Khirbet Solas site, followed by the southern slope of the Slenfeh site, 15.15%, and the southern slope also gained 14.97% for the “Golden Delicious” variety. As for the “Starking” variety, the percentage of dissolved solids increased to 15.09% on the slope. In the eastern part of Khirbet Solas, in Slanfeh it amounted to 14.52% for the western slope, and in Kassab it was 14.86% for the southern slope.